Identification of the functional domains of canine tetherin in antiviral activity against canine influenza virus - Ou, Jiajun; Dai, Yixin; Jiang, Yujie; Dai, Lingzhi; Xu, Liang; Lu, Gang; Lou, Gaoming; Li, Shoujun (Frontiers in Veterinary Science, 2025)
Canine influenza virus (CIV) is a respiratory pathogen that causes fever, coughing, and sneezing in dogs and is continuously circulating in canine populations. Tetherin is an antiviral host restriction factor mediated by interferon, capable of inhibiting the release of enveloped viruses from infected cells. The antiviral mechanism of tetherin is mainly due to its unusual topology, which includes a short N-terminal cytoplasmic tail (CT), a transmembrane (TM) domain, a coiled-coil extra-cellular region (CC), and a C-terminal glycosyl-phosphatidylinositol anchor (GPI). Previous studies have found that canine tetherin has the ability to limit the release of CIV, but its main antiviral domain remains unclear. In the present study, the potential CT, TM, CC, and GPI domains of canine tetherin were predicted through systemic bioinformatic analysis, and mutational variants of canine tetherin based on the four domains were constructed. Confocal microscopy demonstrated that the CT, TM, and CC domains are critical for the cell membrane localization of canine tetherin. The results of in vitro CIV infection experiments showed that the TM region is a critical functional domain of canine tetherin in limiting the replication of CIV. Our study will help better understand the antiviral activity of canine tetherin and the role of the structural domains of canine tetherin in inhibiting the replication of CIV.